Circulating serotypes of dengue virus and their incursion into non-endemic areas of Pakistan; a serious threat. Issue 1 (December 2016) - Ali, Amjad; Ahmad, Habib; Idrees, Muhammad; Zahir, Fazli; Ali, Ijaz
Abstract Background Dengue virus is circulating in Pakistan since 1994, which causes major and minor outbreaks in many areas of the country. The incidence of dengue in Pakistan in past years mainly restricted to parts of Sindh and Punjab provinces. As such, a severe dengue outbreak appeared in Pakistan in 2011, particularly in Punjab province with Lahore as the most hit city (290 deaths). In 2013, for the first time in the history of Pakistan, dengue outbreak erupted in Swat District, Khyber Pakhtunkhwa, which claimed more than 57 lives. Hence this study was conducted to document circulating serotypes of dengue virus in Pakistan in 2011 and 2013 dengue outbreaks in two different territories/areas of the country. Methods In total, 1340 blood samples from people having dengue (ELISA positive) and/or dengue like symptoms from various cities/areas of Punjab and Swat, Khyber Pakhtunkhwa (KP) were collected and analyzed by reverse transcription polymerase chain reaction (RT-PCR) using serotype specific primers. Results The results indicated that all the four dengue virus serotypes were circulating in Punjab Province with highest frequency of DENV-2 (41.64 %) and DENV-3 (41.05 %). Similarly, DENV-2 (41.66 %) and DENV-3 (35.0 %) were dominant serotypes detected in KP-based people lived in Punjab. On the other hand only DENV-2 (40.0 %) and DENV-3 (60.0 %) were detected in Swat District. Furthermore an important observation noted in this study was mixed infection of DENV-2 and DENV-3 in Punjab in 2011 (3.81 %) and in people from KP infected in Punjab (8.33 %) which may account for the high mortality and morbidity rates as compared to previous outbreaks. Over all male population was mostly infected as compared to females and people in the age group between 15 to 45 was the highest infected group. Conclusions The findings of this study indicate that all four serotypes of dengue virus are circulating in Punjab whereas serotypes 2 and 3 introduced for the first time into Swat, KP in 2013; about 600 km away from Lahore, Punjab. Overall dengue virus serotypes 2 and 3 were the major outbreak-causing serotypes in Pakistan in 2011 and 2013. Dengue outbreak in Swat may be the continuation of previous dengue outbreaks in Punjab but it needs further research and investigation.